2014
DOI: 10.1037/a0037361
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal psychotherapy for depressed women with histories of intimate partner violence.

Abstract: Intimate partner violence (IPV) and depression are significant public health problems, yet there are no empirically tested treatments for community-based, clinically depressed women with IPV histories. This uncontrolled pilot study examined the feasibility, acceptability, and preliminary benefits of a community-based administration of brief, group interpersonal psychotherapy (IPT) for depressed women with lifetime histories of IPV (IPT for IPV) to reduce depressive symptoms and improve interpersonal function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 77 publications
0
29
0
2
Order By: Relevance
“…Further, in the studies of IPT for depression in samples of women with trauma histories (Cort et al, 2014;Talbot et al, 2011), there were significant declines in both depression and PTSD, even though the focus of treatment in these investigations was on depression rather than PTSD (whereas in our study the focus was on PTSD rather than depression). Krupnick et al (2008), using the Hamilton Rating Scale for Depression (HAM-D; Hamilton, 1960) in a sample of low-income civilian women, and Markowitz et al (2015), also using the HAM-D in their randomized trial of mostly women civilians, found significant declines in major depression using IPT for PTSD.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Further, in the studies of IPT for depression in samples of women with trauma histories (Cort et al, 2014;Talbot et al, 2011), there were significant declines in both depression and PTSD, even though the focus of treatment in these investigations was on depression rather than PTSD (whereas in our study the focus was on PTSD rather than depression). Krupnick et al (2008), using the Hamilton Rating Scale for Depression (HAM-D; Hamilton, 1960) in a sample of low-income civilian women, and Markowitz et al (2015), also using the HAM-D in their randomized trial of mostly women civilians, found significant declines in major depression using IPT for PTSD.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, the Institute of Medicine (2008) identified exposure therapy as the only intervention with adequate empirical support for PTSD, finding insufficient evidence to support other psychosocial or psychopharmacological approaches. Krupnick et al 57 Recent pilot work (Cort et al, 2014;Bleiberg & Markowitz, 2005;Krupnick et al, 2008), as well as two randomized clinical trials (RCTs) (Markowitz et al, 2015;Talbot et al, 2011), however, point to the potential of IPT as a viable treatment for PTSD. In both Cort et al's (2014) pilot study of IPT for depressed women with histories of intimate partner violence as well as Talbot et al's (2011) RCT for depression in low-income women with childhood sexual abuse (CSA) histories, significant reductions in PTSD were reported.…”
mentioning
confidence: 95%
“…Many prefer to use group intervention [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], leveraging the important therapeutic factors associated with groups like mirroring [ 63 ] and gender-based support. Recent studies have highlighted how evidence-based trauma-focused treatments such as prolonged exposure and cognitive processing therapy can help women who experience IPV [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified the importance of the use of narration with traumatized individuals [ 61 , 62 ] or those who suffered violence “at human hands” [ 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (Cort et al, 2014;Zlotnick, Capezza, & Parker, 2011) have also explored the preliminary effectiveness of an interpersonal therapy (IPT) for women victims of IPV and the results indicate that IPT can be effective in reducing the severity of symptoms of depression among women with a background of IPV. It has been shown that also symptoms of PTSD can be reduced to non-clinical levels (Falsetti, Resnick, Resick, & Kilpatrick, 1993).…”
Section: Interventions For Women Victims Of Intimate Partner Violencementioning
confidence: 99%